Matching supply with demand an introduction to operations management - Cachon, Gérard; Terwiesch, Christian (McGraw-Hill Education, 2013)
This book represents the essential body of knowledge for an introductory operations management course. The guiding principle in the development of Matching Supply with Demand has been "real operations, real solutions."